Celebrating 123 Years of Service to the Lord on a Solid Foundation, 1996 - Riverhill Missionary Baptist Church (Valdosta State University Archives and Special Collections, 1996)
The cover page of a program for the 123rd anniversary of Riverhill Missionary Baptist Church.
This item has 2 pages
Keywords: Lowndes County (Ga.); Church history; River Hill Missionary Baptist Church (Valdosta, Ga.); Baptists; African American churches; Valdosta (Ga.)